"It was at the library; therefore it must be credible": Mapping patterns of undergraduate heuristic decision-making. Issue 2 (3rd April 2018) - McGeough, Ryan; Rudick, C. Kyle
ABSTRACT: In this study, we explore the heuristic decision-making skills of undergraduate students as they incorporate information into their persuasive speeches. We interviewed 26 students enrolled in an introductory communication course to ascertain their information literacy for vetting sources for their public speeches. From their responses, we generated four patterns in students' heuristic decision-making when they made appeals to justify or legitimize their selection of evidence within their persuasive public speech. We conclude by discussing our findings in the context of information literacy scholarship and providing pedagogical advice for instructors who teach public speaking in the introductory communication course.